IMPLEMENTASI KEGIATAN MARKET DAY DALAM MENGEMBANGKAN KEMAMPUAN SOSIAL EMOSIONAL ANAK USIA DINI DI TK MODEL NEGERI PANYABUNGAN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of market day activities in developing early childhood social-emotional skills at TK Model Negeri Panyabungan. The research method used is a qualitative approach with a descriptive type of study. The research subjects include group B children, teachers, and the school principal. Data collection techniques were conducted through observation, interviews, and documentation. The results show that the market day activity is carried out through several stages, namely planning, implementation, and evaluation. During the implementation stage, children act as sellers and buyers, allowing them to interact directly. This activity has been proven to develop children's social-emotional skills, such as cooperation, communication, sharing, emotional regulation, and fostering self-confidence and responsibility. Therefore, market day activities can be an effective learning strategy in developing early childhood social emotional skills.